2011
DOI: 10.1039/c0ce00480d
|View full text |Cite
|
Sign up to set email alerts
|

Growth mechanism and cathodoluminescence properties of indium hydroxide nanocubes synthesized from a simple aqueous solution

Abstract: Single-crystalline In(OH)(3) nanocubes were synthesized in a simple aqueous solution, without using a surfactant, at a temperature as low as 90 degrees C. To elucidate the growth mechanism, the structural evolution of In(OH)(3) nanocubes during the synthesis process were carefully examined. The experimental results showed that the formation of the In(OH)(3) nanocubes is primarily guided by the oriented attachment mechanism, following a zero-dimensional (0D) -> one-dimensional (1D) -> three-dimensional (3D) mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
21
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 58 publications
4
21
2
Order By: Relevance
“…A growth mechanism for In(OH) 3 nanocubes similar to that observed by us has been reported very recently by Jean et al 14 Consistent with our results Jean et al 14 observed that In(OH) 3 nanocubes predominantly form by a multistep OA mechanism. However, in contrast to our findings, Jean et al 14 do not observe InOOH as a second phase behind In(OH) 3 .…”
Section: ■ Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…A growth mechanism for In(OH) 3 nanocubes similar to that observed by us has been reported very recently by Jean et al 14 Consistent with our results Jean et al 14 observed that In(OH) 3 nanocubes predominantly form by a multistep OA mechanism. However, in contrast to our findings, Jean et al 14 do not observe InOOH as a second phase behind In(OH) 3 .…”
Section: ■ Resultssupporting
confidence: 93%
“…However, in contrast to our findings, Jean et al 14 do not observe InOOH as a second phase behind In(OH) 3 . Because Jean et al 14 use urea as the OH − source, they expect the release of OH − and the formation rate of In(OH) 3 particles to be slow.…”
Section: ■ Resultscontrasting
confidence: 85%
“…Criteria of XPS peak assignments for different In-containing species [10][11][12][13][14][15][16][17][18][19][20][21][22]. XPS data of the In metal foils showed slightly lower values (444.3-444.4 eV) for surface oxide (InO x ) over metallic In 0 , compared with ITO and other literature data.…”
mentioning
confidence: 72%
“…In addition, the criteria of XPS peak assignments to various In-containing species including InP, InO x , In(OH) x and InPO x is shown in Table S4. [10][11][12][13][14][15][16][17][18][19][20][21][22] We also collected XPS data of various control samples (InP with native oxide, ITO and In foils) on the same instrument to further support the XPS peak assignment, which are shown in Figure S33-35.…”
Section: X-ray Photoelectron Spectroscopymentioning
confidence: 99%
“…It is known that hollow or big size nanostructures are usually formed by an Ostwald ripening process. [31][32][33] Herein, it should be noted that the outer size of hollow nanoparticles and microtyres is bigger than those of the initial products obtained in 10 min, which differ from the nanorings (60%) and nanodisks (90%). This suggests the nanoparticles and microtyres underwent an Ostwald ripening process after the orientation growth, not a simple etching process.…”
Section: Resultsmentioning
confidence: 99%